One-year outcomes in cardiogenic shock triggered by ventricular arrhythmia: An analysis of the FRENSHOCK multicenter prospective registry - Cherbi, Miloud; Roubille, François; Lamblin, Nicolas; Bonello, Laurent; Leurent, Guillaume; Levy, Bruno; Elbaz, Meyer; Champion, Sebastien; Lim, Pascal; Schneider, Francis; Cariou, Alain; Khachab, Hadi; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Cardiogenic shock (CS) is a life-threatening condition carrying poor prognosis, potentially triggered by ventricular arrhythmia (VA). Whether the occurrence of VA as trigger of CS worsens the prognosis compared to non-VA triggers remains unclear. The aim of this study was to evaluate one-year outcomes (mortality, heart transplantation, ventricular assist devices (VAD)) between VA-triggered and non-VA-triggered CS. Methods: FRENSHOCK is a prospective multicenter registry including 772 CS patients from 49 centers. One to three triggers can be identified in the registry (ischemic, mechanical complications, ventricular/supraventricular arrhythmia, bradycardia, iatrogenesis, infection, non-compliance). Baseline characteristics, management and 1-year outcomes were analyzed according to the VA-trigger in the CS population. Results: Within 769 CS patients included, 94 were VA-triggered (12.2%) and were compared to others. At one year, although there was no mortality difference (42.6% vs 45.3%, HR 0.94 [0.67 - 1.30], p = 0.7), VA-triggered CS resulted in more heart transplantations and VAD (17% vs 9%, p = 0.02). Into VA-triggered CS group, though there was no one-year mortality difference between ischemic and non-ischemic cardiomyopathies (42.5% vs 42.6%, HR 0.97 [0.52 – 1.81], p = 0.92), non-ischemic cardiomyopathy led to more heart transplantations and VAD (25.9% vs 5%, p = 0.02). Conclusion: VA-triggered CS did not show higher mortality compared to other triggers but resulted in more heart transplantation and VAD at one year, especially in non-ischemic cardiomyopathy, suggesting the need for earlier evaluation for mechanical circulatory support or heart transplantation in that population. NCT02703038